EVALUATION OF REGIONAL REVENUE AND EXPENDITURE BUDGETS IN THE PALU CITY GOVERNMENT - Gollah, Shery Natalia; Paranoan, Selmita; Yamin, Nina Yusnita; Masruddin, Masruddin (ISAS, 2025)
Post-calamity 2018 and the COVID-19 pandemic caused the fiscal performance of Palu City Government to change significantly. For this study, the dynamics of the 2019-2023 Palu City APBD are to be evaluated through growth and variance analysis in an attempt to provide responsive fiscal policy recommendations. Quantitative methods apply by processing the secondary data with APBD reports. Results showed an